Incidence and predictors of obstetric and fetal complications in women with structural heart disease. Issue 20 (4th April 2017) - van Hagen, Iris M; Roos-Hesselink, Jolien W; Donvito, Valentina; Liptai, Csilla; Morissens, Marielle; Murphy, Daniel J; Galian, Laura; Bazargani, Nooshin Mohd; Cornette, Jérôme; Hall, Roger; Johnson, Mark R
Abstract : Objective: Women with cardiac disease becoming pregnant have an increased risk of obstetric and fetal events. The aim of this study was to study the incidence of events, to validate the modified WHO (mWHO) risk classification and to search for event-specific predictors. Methods: The Registry Of Pregnancy And Cardiac disease is a worldwide ongoing prospective registry that has enrolled 2742 pregnancies in women with known cardiac disease (mainly congenital and valvular disease) before pregnancy, from January 2008 up to April 2014. Results: Mean age was 28.2±5.5 years, 45% were nulliparous and 33.3% came from emerging countries. Obstetric events occurred in 231 pregnancies (8.4%). Fetal events occurred in 651 pregnancies (23.7%). The mWHO classification performed poorly in predicting obstetric (c-statistic=0.601) and fetal events (c-statistic=0.561). In multivariable analysis, aortic valve disease was associated with pre-eclampsia (OR=2.6, 95%CI=1.3 to 5.5). Congenital heart disease (CHD) was associated with spontaneous preterm birth (OR=1.8, 95%CI=1.2 to 2.7). Complex CHD was associated with small-for-gestational-age neonates (OR=2.3, 95%CI=1.5 to 3.5). Multiple gestation was the strongest predictor of fetal events: fetal/neonatal death (OR=6.4, 95%CI=2.5 to 16), spontaneous preterm birth (OR=5.3, 95%CI=2.5 to 11) and small-for-gestational age (OR=5.0, 95%CI=2.5 to 9.8). Conclusion: The mWHO classification is not suitable for prediction of obstetric and fetal events in women with cardiac disease. Maternal complex CHD was independently associated with fetal growth restriction and aortic valve disease with pre-eclampsia, potentially offering an insight into the pathophysiology of these pregnancy complications. The increased rates of adverse obstetric and fetal outcomes in women with pre-existing heart disease should be highlighted during counselling.